Selecting behaviour change priorities for trachoma 'F' and 'E' interventions: A formative research study in Oromia, Ethiopia. - Katie Greenland; Sian White; Katina Sommers; Adam Biran; Matthew J Burton; Virginia Sarah; Wondu Alemayehu (Public Library of Science (PLoS), 2019)
Background Trachoma is the leading infectious cause of blindness. However, little is known about the behavioural and environmental determinants of transmission of the causative organism, Chlamydia trachomatis. We conducted formative research in a trachoma hyper-endemic area of Ethiopia to explore the behaviours which are likely to contribute to trachoma transmission and map their determinants. Methodology/principal findings Data on water use, hygiene, defecation, and sleeping arrangements were collected from five communities during the dry and rainy seasons in 2016. Data collection involved direct observation in households (n = 20), interviews with caregivers (n = 20) and focus group discussions (n = 11). Although several behaviours that likely contribute to trachoma transmission were identified, no single behaviour stood out as the dominant contributor. Hygiene practices reflected high levels of poverty and water scarcity. Face washing and soap use varied within and between households, and were associated with other factors such as school attendance. Children's faces were rarely wiped to remove nasal or ocular discharge, which was not perceived to be socially undesirable. Bathing and laundry were performed infrequently due to the amount of time and water required. Open defecation was a normative practice, particularly for young children. Latrines, when present, were poorly constructed, maintained and used. Young children and parents slept closely together and shared bedding that was infrequently washed. Conclusions/significance Existing norms and enabling factors in this context favour the development of interventions to improve facial cleanliness as more feasible than those that reduce unsafe faeces disposal. Interventions to increase the frequency of bathing and laundry may also be infeasible unless water availability within the home is improved.